Political Participation of Disability Communities in Makassar Mayor Election 2018 - Rafika Abrianti; Nuryanti Mustari; Fatmawati; Ahmad Taufik (Mengeja Indonesia Publisher, 2021)
This study aims to determine the political participation of people with disabilities in the general election of the mayor of Makassar in 2018 and to determine the factors supporting and inhibiting political participation of people with disabilities in the election of the mayor of Makassar. The type of research is descriptive qualitative, which describes the political participation of people with disabilities in the general election of the mayor of Makassar in 2018 descriptively. The data collection techniques used are observation, interviews, and documentation. In this study, there were ten primary informants. Data analysis techniques by analyzing the results of the processed data are interpreted in the form of narration. While the validation of the data using triangulation. The results showed that the participation of people with disabilities in the Makassar mayoral election in 2018 was quite good because their participation was increasing from year to year. The supporting factors of political participation are the community environment and political awareness, and the completeness of the ballot. At the same time, the inhibiting factor is the lack of relevant data regarding the number of people with disabilities who take part in the election.